Problems with atonement : the origins of, and controversy about, the atonement doctrine - Finlan, Stephen (Collegeville, Minn. : Liturgical Press, 2005)
"Examines the origins and outcomes of the Christian doctrine of atonement : its biblical foundations, development, and theological questions surrounding it, including questions about its relationship to the Incarnation"--Provided by publisher.
Sacrifice and scapegoat -- Paul's use of cultic imagery -- Atonement after Paul -- Rationalizing the atonement doctrine -- The Incarnation.
"A Michael Glazier book."
Includes bibliographical references (p. 125-134) and indexes.
Keywords: Atonement -- History of doctrines; x